Integration Of Hirka Packaging As A Physical Output Of The System E-Commerce In Improving Customer Experience - Fadillah, Ismail Hudan; Soegoto, Eddy Soeryanto; Wahdiniwaty, Rahma; Sumitra, Irfan Dwiguna; Bachtiar, Adam Mukharil (International Journal of Research and Applied Technology (INJURATECH), 2025)
The development of e-commerce as an applied information system has changed the interaction pattern between brands and consumers, where user experiences are increasingly mediated by non-physical digital processes. This condition creates limitations in conveying material value, product quality, and brand character, especially for products that emphasize material aspects and an artisan approach. This study aims to analyze the role of packaging as a physical output in the e-commerce system architecture and its contribution to enhancing the customer experience value of the local leather shoe brand HIRKA. The study uses a qualitative approach with a case study method. Data collection was carried out through observations of the marketplace system and HIRKA packaging design, in-depth interviews with brand owners, and literature studies related to e-commerce information systems and technology-based customer experience. The results show that packaging functions as an extension of the information system that translates data, visual representations, and digital narratives into a physical post-purchase experience. The integration between the e-commerce system and packaging design creates continuity between the digital process and the physical output, narrowing the gap in user experience, and increasing customer perceptions of value, trust, and satisfaction. These findings emphasize that evaluation of e-commerce system performance needs to consider the quality of integration between the digital system and the physical output as part of the overall customer experience.